2021
DOI: 10.6007/ijarbss/v11-i4/9842
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Writing Anxiety and the Pedagogical Use of Online Learning Medium among Malaysian University Students

Abstract: According to United Nations in 2020, the pandemic of COVID-19 has caused the largest disruption of education systems in history. The sudden transition from traditional classroom to online classroom has caused many students to become anxious with their learning especially when they have to learn writing skills through several online mediums such as instant messenger (e. g. Whatsapp and Telegram), social media (e. g. Facebook, Instagram, Twitter and YouTube), live meeting session (e. g. Google Hangouts Meet, Zoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Among them, "staying calm and relax", "focusing on the given topic", "preparing in advance", "E-learning setting", "asking for the classmates' help", "asking for the lecturer's help" and "time management", were reported as the most frequent ones, followed by "staying confident", "positive attitude", "research about the topic", "preparing an outline before writing", and "developing writing skills" were mentioned as the least frequent ones amongst the students. These strategies had been explored by previous researchers including Qashoa (2014), Wu and Lin (2016), Jawas (2019), Wahyuni et al (2019), Kamaruddin et al (2021), and Wern and Rahmat (2021). These studies had also identified "taking a deep breath", "taking some time off from writing task", "getting some entertainment", "process writing approach", "positive error correction", and "vocabulary knowledge enhancement" as the most frequent writing anxiety coping strategies.…”
Section: Coping Strategiesmentioning
confidence: 99%
“…Among them, "staying calm and relax", "focusing on the given topic", "preparing in advance", "E-learning setting", "asking for the classmates' help", "asking for the lecturer's help" and "time management", were reported as the most frequent ones, followed by "staying confident", "positive attitude", "research about the topic", "preparing an outline before writing", and "developing writing skills" were mentioned as the least frequent ones amongst the students. These strategies had been explored by previous researchers including Qashoa (2014), Wu and Lin (2016), Jawas (2019), Wahyuni et al (2019), Kamaruddin et al (2021), and Wern and Rahmat (2021). These studies had also identified "taking a deep breath", "taking some time off from writing task", "getting some entertainment", "process writing approach", "positive error correction", and "vocabulary knowledge enhancement" as the most frequent writing anxiety coping strategies.…”
Section: Coping Strategiesmentioning
confidence: 99%